Group theory for social workers : an introduction - Heap, Ken, 1929- (Social work series., 1977)
Presents aspects of group theory from the disciplines of social and developmental psychology, small-group psychology, psycho-analytical theory and practice. The concepts discussed are chosen for their relevance to understanding the behavior of clients who are members of groups in social work treatment, and the book is extensively illustrated by case extracts from social work practice.